Tumorska hipoglikemija - premalo prepoznano nujno stanje - Ećimović, Patricija (Zdravniški vestnik, 2008)
Background Tumor hypoglycemia is a rare and easily misdiagnosed non-diabetic hypoglycemia that newly arises in a cancer patient. Itćs resistant to symptomatic treatment so it is important to investigate for its causes to treat it successfully. Tumor hypoglycemia can be caused by insulinoma, by tumor secretion of insulin-like substances (Insuline-like growth factor 2, IGF-2), liver metastases, cachexia or paraneoplastic endocrine abnormalities. Conclusions We are presenting a review of current literature on tumor hypoglycemia that highlights the importance of investigating causative mechanisms in order to control it.
Keywords: Cachexia; diagnostika; Etiology; Hipoglikemija; Hypoglycemia; Insulin-Like Growth Factor Ii; Insulinoma; Inzulinom; Inzulin-podobn, rastni faktor II; Jetra, novotvorbe; Kaheksija; Liver Neoplasms; Neoplasms; Novotvorbe; onkologija; Paraneoplastic Syndromes; Paraneoplastični sindromi; Secondary; tumor; tumorska hipoglikemija